Pengaruh Pendapatan Asli Daerah dan Dana Alokasi Umum Terhadap Belanja Modal Pada 19 Kabupaten dan Kota di Sumatera Barat - Joni Fernandes; Devi Oktavia (Jurnal Ilmiah Pendidikan Scholastic, 2021)
The low absorption of the budget in capital expenditures can have an impact, including, for example, the poor local infrastructure that is currently owned and the absence of a significant additional number of projects in the new infrastructure sector, the absence of basic infrastructure such as ports, roads, clean water processing and generators electricity. The purpose of this study was to determine how much influence local revenue and general allocation funds have on capital expenditures in 19 districts and cities in West Sumatra for the 2015–2019 period. Total sampling method is used for the sampling technique and obtained 95 data. The Central Bureau of Statistics of West Sumatra Province is a place for data collection through the website www.sumbar.bps.go.id. Panel data regression analysis is the analysis method used with the help of the E-Views 8 application. After the Hausman-Test was carried out, it was decided to use the Fixed Effect Model method. The results showed that there was a positive effect of PAD and DAU on capital expenditures, both individually and collectively.